Sistem Otomatisasi Mesin Filling Alers Sebagai Paste Filling Machine Menggunakan PLC Omron - wiharja, Ujang; Himawan, Ilham (JURNAL ELEKTRO, 2025)
Pharmacy is a basic human need that has evolved alongside human civilization. With the advancement of technology and information, pharmacy has developed into a promising profession. Initially, it was just a service aimed at protecting people from suffering. The pharmaceutical industry is a business entity that has been authorized by the Minister of Health to engage in the manufacturing of drugs or medicinal substances. The production of high-quality drugs or medicinal substances requires machinery with advanced technology to ensure performance. This certainly helps save time, human labor, and costs during the production process. In this final project research, an automation system has been developed for the Filling Alers machine, specifically the Paste Filling Machine Type 1624. The Filling Alers PFM Type 1624 machine currently requires manual assistance or an operator during the filling process of products into containers. An automated system will be created for this process using an Omron CP1E PLC. With this automation system, the filling process will run automatically without needing human or operator intervention. The results of the product filling will adhere to the established weight standards during production. The product's weight will remain stable between 455 gr and 461 gr, ensuring that the product weight does not fall below 455 gr or exceed 461 gr. This eliminates the need for additional work by the operator to adjust the product amount when the weight is either below 455 gr or above 461 gr.